PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII2 SMP NEGERI 17 PEKANBARU - Alvini Lestari; Rini Dian Anggraini; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to improve learning process and increase student’s mathematical achievement through implementation of Problem Based Learning (PBL) Model. This type of research is Classroom Action Research with two cycle.The research was conducted in class VII2 SMP Negeri 17 Pekanbaru in the first semester of the 2018/2019 academic year. The subject of this research consist of 33 students, there are 18 female students and 15 male students. The research instrument consists of learning materials and instruments for collecting data. Learning materials used in this research are the Syllabus, Lesson Plan and Activity Sheets. Instrument data collectors used in this research are observation sheet and mathematical achievement test. Application of PBL model also gives positive impact on the implementation of learning process that students become more active in learning activities so that learning is not centered on the teacher. Students are also trained to build their own knowledge and can find their own mathematical concepts through the presentation of problems close to the student's real life. The percentage of students which ispass Minimum Mastery Crieria (MMC) increase from 42,42% to 60,6% at the first test and to 81,8% at the second test. This research concludes that the implementation of PBL improved the learning process and the student’s mathematical achievement atclass VII2 SMP Negeri 17 Pekanbaru. PBL model can be used as an alternative to learning, because through this learning can improve the learning process and mathematical achievement of the students.Key Words: Classroom Action Research, Problem Based Learning models, Learning outcomes,Learning Process